Fawatih As Suwar: Menyingkap Keindahan Kata Pertama dalam Surah Al-Qur’an - Muthiah, Aniqotul (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The results of this study describe that the undeniable beauty of the Qur'an is the first word in the surah of the Qur'an whose study has attracted the attention of scholars from both Muslim and Orientalist circles. Of course, the selection of certain verses as the opening of the letter is accompanied by wisdom, including awareness of the importance of choosing the right sentence so that the communication of the Qur'an with its communicants can run well and the messages of Divine revelation can be conveyed. Literary and language experts know the importance of selecting the right sentence as an opener for the conversation and the Qur'an which is confirmed as a text with the highest unmatched literature certainly does not neglect this. The study uses a literature study method. The purpose of this study is to add discourse on the wisdom and beauty of the words chosen as the opening of the surah so that it can be an additional discourse for us to realize the perfection and i'jaz of the Qur'an in terms of its language.